Agroecology Initiative policy tracker guideline and tool - Place, Frank (CGIAR System Organization, 2023)
The agroecology policy tracker is designed to accommodate policy and institutional objectives and progress at the national and Agroecology Living Landscape (ALL) level. It will have to be decided which policy making or administrative level best corresponds to the ALL in each country. In Kenya for example, there has been alignment in the selection of the ALL with the administrative level of a county. Therefore, the team should review policy and institutional opportunities at the county level as well as national level. In India, it would be the state level. In countries with more devolution of policy making authority to local levels, the local level will be an important one. It may be less so in more centralized governments where the role of local public agencies is mainly to implement national policies and programs.